Congenital Bilateral Perisylvian Syndrome Associated with Pierre Robin Sequence: a Case Report - Castro-Murillo, Julio Cesar; Gómez-Guzmán, Enid Leticia; Rojas-Cerón, Christian Andrés (Iatreia)
Introduction: Pierre Robin sequence is characterized by the classic triad of congenital micrognathia, glossoptosis, and airway obstruction. It is caused by various etiologies, including cortical development malformations as seen in congenital perisylvian syndrome. Clinical Case Presentation: We report a case of a 31-week preterm newborn girl who exhibited the classic triad of Pierre Robin sequence during physical examination, later developing complications such as epileptic seizures, airway obstruction, and swallowing disorder. During the etiological investigation, cerebral magnetic resonance imaging revealed bilateral polymicrogyria, confirming a diagnosis of bilateral perisylvian syndrome. Conclusions: Cortical development malformations, such as congenital bilateral perisylvian syndrome, are part of the etiological spectrum in Pierre Robin sequence, especially those presenting with pseudobulbar paralysis, epileptic seizures, and central origin hypotonia.